Experimental and numerical studies for parameters identification of direct current motor - Mohamad Nazir Abdullah; Mohd Khairunaz Mat Desa; Elmi Abu Bakar; Mohammad Nishat Akhtar (Institute of Advanced Engineering and Science, 2022)
Direct current (DC) motors are widely used in many applications especially those require a speed control, direction and closed-loop control system. In electric vehicle drive system, DC motor is commonly used for the propulsion of low power (<250 W) electric bicycle (e-bike) because it can operate directly from rechargeable batteries with a smart controller. In driving an e-bike in a closed loop control system, it is important to identify and estimate the dynamic of electrical and mechanical parameters. In this paper, the parameters such as armature resistance, armature inductance, back emf constant, torque constant, moment of inertia and viscous friction coefficient are ideally identified using dynamic responses experiments and tests focusing on no load motor and transient input tests. The motor is then modeled in MATLAB/Simulink using the identified motor parameters and its open loop speed and current responses are studied.